Analysis of the influence of methods for controlling power unit with a pressurized water reactor for axial offset - Максимов, Максим Витальевич; Фощ, Тимур Витальевич; Никольский, Марк Витальевич (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with analyzing the influence of the methods for controlling power unit with the VVER-1000 power unit in a maneuverable mode on a quantitative measure of stability, namely on the size of axial offset. Automated systems for controlling power units with the VVER-1000 reactor in maneuvering with such control programs as: with a constant average temperature of the coolant in the first loop, with a constant pressure in the second loop, with a sliding pressure in the second loop, with a constant water temperature at the input to AKZ of the reactor, were described. Also, the graphs of the reactor axial offset variations in a maneuverable mode from 100% to 80 % and vice versa were made and presented. It was found that in stationary automated control systems of power units with the VVER-1000 reactor, the axial offset is unstable and may lead to a decrease in stability and reliability of the reactor. The improved automated control systems allow maintaining sufficiently the axial offset constants and the necessary parameters of the control program on the whole range of power unit maneuvering.